Sørena Kierkegaarda pojęcie lęku - Paweł Eugeniusz Gazda (Warszawskie Studia Teologiczne)
In Either/Or Søren Kierkegaard introduced the concept of absolute choice, and them in Fear and Trembling he wrote a lot about the leap of faith, nevertheless neither Judge Wilhelm nor Johannes de Silentio gave the motive that could have brought a particular man to make the choice of his own self in order to have an authentic life. For this reason – as Vigilius Haufniensis – Kierkegaard wrote The Concept of Anxiety to answer the following questions: what prompts a man to choose himself? is it something that impels him “from the outside”? or maybe – some "internal" persecutory power? and what testifies to the man the possibility of making such a choice? Therefore, the purpose of this work is to analyze the Kierkegaard's concept of anxiety (in the context of his interpretation of the Fall of First Man) as the main condition and the explanation of the absolute choice.